2012
DOI: 10.1371/journal.pcbi.1002744
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of Human Immunodeficiency Virus Type 1 Therapies Based on Conditionally Replicating Vectors

Abstract: Efforts to reduce the viral load of human immunodeficiency virus type 1 (HIV-1) during long-term treatment are challenged by the evolution of anti-viral resistance mutants. Recent studies have shown that gene therapy approaches based on conditionally replicating vectors (CRVs) could have many advantages over anti-viral drugs and other approaches to therapy, potentially including the ability to circumvent the problem of evolved resistance. However, research to date has not explored the evolutionary consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…Specifically, the analysis indicates that DIPs that suppress HIV replication via genome stealing will be unstable due to divergence between the HIV-1 DIS and the DIP DIS (i.e., interference and recombination via genome heterodimerization are minimized). This analytical finding raises doubts regarding the validity of a recent computational model that analyzes the evolutionary stability of conditionally replicating HIVs (i.e., DIPs) based exclusively on genome stealing (72). That DIS divergence is, in principle, possible is supported by the finding that different HIV-1 subtypes display diverse DIS sequences (73).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the analysis indicates that DIPs that suppress HIV replication via genome stealing will be unstable due to divergence between the HIV-1 DIS and the DIP DIS (i.e., interference and recombination via genome heterodimerization are minimized). This analytical finding raises doubts regarding the validity of a recent computational model that analyzes the evolutionary stability of conditionally replicating HIVs (i.e., DIPs) based exclusively on genome stealing (72). That DIS divergence is, in principle, possible is supported by the finding that different HIV-1 subtypes display diverse DIS sequences (73).…”
Section: Discussionmentioning
confidence: 99%
“…Ke and Lloyd-Smith for their letter (1) highlighting the critical discrepancies between the claims of their recent simulation study (2) and the results derived by evolutionary calculations in our analytic study (3). In contrast to our direct calculations, Ke and Lloyd-Smith argue that therapeutic interfering particles (TIPs)-generated by conditionally replicating vectors-would stably cross dimerize with HIV and indefinitely coevolve with the virus.…”
mentioning
confidence: 67%
“…Their analyses are illuminating, particularly in highlighting the importance of multiple DIP infections of a cell and the possible role of "capsid stealing" by the DIPs. However, they state that the coevolution of HIV-1 and DIPs has not been explored previously while simultaneously raising "doubts regarding the validity" of our recent study of this problem (2). We wish to clarify two key issues and broaden the discussion.…”
mentioning
confidence: 95%
“…Furthermore, in vitro studies have shown that mutated DIS sequences substantially decrease the efficiency of HIV-1 packaging and/or cellular infectivity (at least for the subset of mutations that have been studied) (5-8). Our recent work integrated these factors and showed that a genome-stealing strategy can be coevolutionarily stable, though we emphasized that experimental confirmation will be needed for particular DIP constructs (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation